Abscisic acid (ABA) receptors: Light at the end of the tunnel - Muschietti, Jorge Prometeo (2010)
The plant hormone abscisic acid (ABA) plays a role in several aspects of plant growth and development. Understanding how this hormonal stimulus is sensed and transduced turned out to be one of the major tasks in the field of plant signaling. A series of recent papers proposed several different proteins that could receive the ABA signal and initiate the signaling cascade. The winner appears to be PYR/PYL/RCAR (PYrabactin Resistance/PYrabactin Resistance-Like/Regulatory Component of Abscisic acid Receptor) proteins, as crystal structures were recently published. The crystal structures support the idea that upon ABA binding to a PYR/PYL/RCAR protein, the activity of a phosphatase 2C, with known repressive activity on ABA signaling, is inhibited.